Spontaneous Relaxation of Heteroepitaxial Thin Films by van der Waals‐Like Bonding on Te‐Terminated Sapphire Substrates. Issue 45 (20th October 2020) - Jovanovic, Stephen M.; El‐Sherif, Hesham M.; Bassim, Nabil D.; Preston, John S.
Abstract: Here the novel direct heteroepitaxial growth method of a 3D heteroepitaxial system is demonstrated on a 3D substrate, CdTe (111)/Al2 O3 (0001), which forms a spontaneous vdW‐like bond at the interface, instead of the two 3D crystals being strongly bound. Despite a large lattice mismatch, the thin films are single crystals and maintain high quality due the compliance of the interface which accommodates strain. This weak bonding interface is accomplished by the self‐assembly of a pseudomorphic chalcogenide layer on the sapphire surface during growth. Since the vdW‐like interface forms spontaneously in situ during growth, it is easily scalable to large wafer sizes, without the need to layer transfer 2D materials onto the growth substrate for remote epitaxy. Further, the weak adhesion of the films on the substrates allow for epitaxial film transfer to a variety of other substrates, leaving the original growth substrate for future reuse. This type of 3D/3D vdW‐like interface is exploitable as a compliant interlayer for additional epitaxy, and may even be observable directly in other material systems grown on complex oxides, allowing for the production of large area high quality freestanding and layer transferred epitaxial devices for material systems not currently possible by conventional processing techniques. Abstract : Spontaneous van der Waals‐like bonding occurs during the growth of a 3D/3D heteroepitaxial system, CdTe(111)/Al2 O3 (0001), creating a compliant interface to produce high quality films despite a large lattice mismatch. This discovery provides mechanisms to develop flexible exfoliated heterostructures, grow material systems where conventional substrates are not available, and create semiconductor‐oxide van der Waals contacts.